The out of school literacy practices of children with specific learning disabilities : a case study - Herman, Ilona (School of Education, 2015)
A number of studies have been conducted on in-school and out of school literacy practices in the United Kingdom and North America within a sociocultural framework. However, there is very little research on the out of school literacy practices of children in South Africa and there is a general dearth of research on the out of school literacy practices of children with specific learning disabilities, both locally and internationally. Aiming to make a contribution towards filling this gap, this investigation explores the out of school literacy practices of children with specific learning disabilities (SLD) attending a special needs school in South Africa.